Menilik Efektivitas Mediasi dan Tantangan Mewujudkan Keadilan Substantif di Pengadilan Agama Metro - Meisa Hidayah; Elfa Murdi ana; Nyimas Lidya Putri Pertiwi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Institut Agama Islam Negeri Sultan Amai Gorontalo, 2026)
This study examines the persistent failure of court-annexed mediation in the Religious Court of Metro, where only 34 out of 505 mediated cases in 2024 reached an agreement. Although mediation is mandated under Supreme Court Regulation No. 1 of 2016 as a strategic mechanism to promote peaceful, efficient, and substantive dispute resolution, its practical implementation often falls short of these ideals. The research addresses a key gap in existing scholarship, which has predominantly focused on procedural obstacles and the general causes of mediation failure, but rarely on the strategic role of judge-mediators in realizing substantive justice within the socio-psychological dynamics of divorce disputes. Using a qualitative field method, data were collected through in-depth interviews with certified judge-mediators and disputing parties, complemented by document analysis. The findings reveal that mediation failures stem from external interventions, the parties’ emotional instability, limited mediator competence, and a tendency toward formalistic mediation practices. Conversely, successful mediations rely on strategic judge interventions, including cultural-religious approaches, facilitative dialogue, and the reinforcement of good faith. The study recommends strengthening mediator training, enhancing institutional support, and integrating culturally sensitive strategies to ensure that mediation functions not merely as a procedural requirement but as a genuine avenue for substantive justice.